Accurate H‐atom parameters for the two polymorphs of l‐histidine at 5, 105 and 295 K. Issue 5 (21st September 2021) - Novelli, Giulia; McMonagle, Charles J.; Kleemiss, Florian; Probert, Michael; Puschmann, Horst; Grabowsky, Simon; Maynard-Casely, Helen E.; McIntyre, Garry J.; Parsons, Simon
Abstract : Single‐crystal neutron and X‐ray diffraction data for the orthorhombic and monoclinic polymorphs of the amino acid l ‐histidine have been collected at 5, 105 and 295 K. The neutron structural models are compared with those refined with the new Hirshfeld atom refinement method implemented in NoSpherA2 . Abstract : The crystal structure of the monoclinic polymorph of the primary amino acid l ‐histidine has been determined for the first time by single‐crystal neutron diffraction, while that of the orthorhombic polymorph has been reinvestigated with an untwinned crystal, improving the experimental precision and accuracy. For each polymorph, neutron diffraction data were collected at 5, 105 and 295 K. Single‐crystal X‐ray diffraction experiments were also performed at the same temperatures. The two polymorphs, whose crystal packing is interpreted by intermolecular interaction energies calculated using the Pixel method, show differences in the energy and geometry of the hydrogen bond formed along the c direction. Taking advantage of the X‐ray diffraction data collected at 5 K, the precision and accuracy of the new Hirshfeld atom refinement method implemented in NoSpherA2 were probed choosing various settings of the functionals and basis sets, together with the use of explicit clusters of molecules and enhanced rigid‐body restraints for H atoms. Equivalent atomic coordinates and anisotropic displacement parameters were compared and found to agree well with those obtained from the corresponding neutron structural models.